PENGARUH HARGA, PENGATURAN TEMPAT, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PASAR RAYA MEDAN MEGA TRADE CENTER - Hasibuan, Leo Jabonor; Manalu, Darma; Sinaga, Kepler; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this study was to determine and analyze how much influence price, place setting and product quality have on purchasing decisions at market Raya Medan Mega Trade Center, this research was conducted at market Raya Medan Mega Trade Center, this research was conducted by researchers in March 2025. This study uses a quantitative approach and uses data collection techniques by distributing questionnaires and analyzed using instrument tests, classical assumption tests, multiple linear analysis, hypothesis testing. The population in this study were prospective buyers and consumers who bought at market Raya Medan Mega Trade Center, the sample in this study was 96 samples, while the results of the study were Price has a significant effect on purchasing decisions because, Sig value. = 0.000 <0.05, then H₀ is rejected and H₁ is accepted. This means that price has a significant effect on purchasing decisions, place settings have a significant effect on purchasing decisions because, Sig value. = 0.026 <0.05, then H₀ is rejected and H₁ is accepted. This means that there is a significant influence between place settings and purchasing decisions, Product Quality has a significant effect on purchasing decisions because, Sig value. = 0.000 <0.05, so H₀ is rejected and H₁ is accepted. So, product quality has a significant effect on purchasing decisions, Price, Place Settings and Product Quality simultaneously or together have an effect on purchasing decisions, because the calculated F value is 85.403 with a significance value (Sig.) of 0.001. Because the value of Sig. <0.05, then H₀ is rejected and H₁ is accepted. This means that there is a significant simultaneous influence between Price, Place Settings, and Product Quality on Purchasing Decisions. These results indicate that together the three independent variables are able to explain the variations that occur in consumer purchasing decisions at market Raya Medan Mega Trade Center convincingly and significantly, The results of the coefficient of determination (R²) can be seen that the coefficient of determination obtained an R value of 0.858 and R² of 0.736. This means that 73.6% of the variation in purchasing decisions can be explained by the price, place setting, and product quality variables in the regression model used. While the rest, which is around 26.4%, is influenced by other factors that are not explained in this research model.